Innovative application of particle swarm algorithm in the improvement of digital enterprise management efficiency - Shengnan Zhang (Systems and Soft Computing)
At present, the management of most enterprises still adopts the traditional business model, which is difficult to meet the requirements of modern informatization. To effectively improve the efficiency of digital enterprise management and solve the limitations of traditional management methods in resource allocation, decision-making, and process optimization, an experiment is proposed for a digital enterprise innovation management method based on Particle Swarm Optimization. The research results show that the method is applied to the enterprise for simulation experiments, and the efficiency obtained after using the method is as high as 99.5 %, which is nearly 2 % higher than the enterprise management efficiency obtained before the method is not used. The results show that the proposed Particle Swarm Optimization has high reliability and accuracy for improving the management efficiency of digital enterprises, and can provide new research directions and ideas for the development and progress of enterprises in the Internet era.